Entre o secreto e o discreto: A comunicação organizacional para a gestão da (in)visibilidade da Maçonaria (Intercom - Brazilian Journal of Communication Sciences, 2024)
Under the theme of communication in the management of visibility in organizations, we aim to understand how Freemasonry manages its (in)visibility from its organizational communication processes. For that, we have used elements of symbolic interactionism (MEAD, 1982; BLUMER, 1982) and resorted to theoretical contributions from organizational communication (BALDISSERA, 2009; 2017) and the notion of secrecy (SIMMEL, 1999; DESPRET, 2011). In methodological terms, we have mobilized secondary data from research carried out by Vinhola (2021) and analyzed them using the stage/backstage metaphor by Goffman (2002) in conjunction with the dimensions of organizational communication by Baldissera (2009). The main inference is that the management of (in)visibility of the masonic organization is based on the basic logic of discreet communication.